Entwicklung der Erwerbsbeteiligung bis 2030 unter Berücksichtigung von Änderungen im Bildungsverhalten und rezenten Pensionsreformen - Thomas Horvath; Helmut Mahringer (Austrian Institute of Economic Research (WIFO), 2014)
– The Austrian population will continue to grow over the next decades. At the same time the number of working age people is predicted to decline until 2030. In how far this demographic change will translate into changes in the total number of people in the labour force (employed plus unemployed people) depends mainly on their labour market attachment. This paper analyses the development of labour force participation rates explicitly accounting for changes in the education structure, long-term trends in participation rates and recent tightenings in pension law. These factors are shown to affect labour force participation rates markedly. A reduction in the total number of people in the workforce until 2030 seems unlikely when accounting for these facts.
Keywords: 330; Arbeitskräfteangebot; Demographie; Bildung; Pensionsreform